Letter to the Publisher of Phenomena - Schwartz, Stephan (Journal of Scientific Exploration, 2017)
Editor’s Note: The following is a letter Stephen Schwartz sent to the publisher of Phenomena, prior to the book’s release, after being sent a galley of the section of the manuscript in which his work was represented. The letter itself explains the context. —————————————- 18 November 2016 Little Brown Market Place Center 3 Center Plaza Boston, MA 02108 enclosures: as above [below here in the JSE] RE: PHENOMENA Let me begin by telling you that I had hoped I would not have to write this letter, but I have no choice because as a scientist and historian I place accuracy, both factual and contextual, as a first priority. Some months ago I had a brief telephone interview with one of your authors, Annie Jacobsen. I heard nothing further until I received an email on 16 November attached to which was a selection of pages for the upcoming book Phenomena covering my research with the admonishment my edits must be in her hands by “Sunday/Monday”—basically three days in the future. Since then I have exchanged 13 emails, and had three quite acrimonious telephone conversations, all very hurried because Ms. Jacobsen couldn’t talk at length. The first thing I noticed when I read pages 191–199 (which I enclose) that covered my research was that the narrative of what happened bore very little tangency to real events, or real context. Ms. Jacobsen made it explicitly clear that she was not interested “in your interpretation of events, only specific corrections.” In response I pointed out multiple name misspellings, as well as incorrect institutional affiliations. The funny thing about all of this was that her pages were describing events that occurred 40 years ago about which much has already been published. Indeed, Little Brown published my chapter on this entire event in 1984, in Stories From Omni. I also wrote about these experiments in my book Opening to the Infinite, as well as in numerous research papers presented at science conferences in several disciplines. A high school sophomore in five minutes of Googling could have obtained the correct information.